The long noncoding RNA ROCKI regulates inflammatory gene expression. (27th March 2019) - Zhang, Qiong; Chao, Ti‐Chun; Patil, Veena S; Qin, Yue; Tiwari, Shashi Kant; Chiou, Joshua; Dobin, Alexander; Tsai, Chih‐Ming; Li, Zhonghan; Dang, Jason; Gupta, Shagun; Urdahl, Kevin; et al.
Abstract: Long noncoding RNAs (lncRNAs) can regulate target gene expression by acting in cis (locally) or in trans (non‐locally). Here, we performed genome‐wide expression analysis of Toll‐like receptor (TLR)‐stimulated human macrophages to identify pairs of cis ‐acting lncRNAs and protein‐coding genes involved in innate immunity. A total of 229 gene pairs were identified, many of which were commonly regulated by signaling through multiple TLRs and were involved in the cytokine responses to infection by group B Streptococcus . We focused on elucidating the function of one lncRNA, named lnc‐MARCKS or ROCKI (Regulator of Cytokines and Inflammation), which was induced by multiple TLR stimuli and acted as a master regulator of inflammatory responses. ROCKI interacted with APEX1 (apurinic/apyrimidinic endodeoxyribonuclease 1) to form a ribonucleoprotein complex at the MARCKS promoter. In turn, ROCKI –APEX1 recruited the histone deacetylase HDAC1, which removed the H3K27ac modification from the promoter, thus reducing MARCKS transcription and subsequent Ca 2+ signaling and inflammatory gene expression. Finally, genetic variants affecting ROCKI expression were linked to a reduced risk of certain inflammatory and infectious disease in humans, including inflammatory bowel disease and tuberculosis. Collectively, these data highlight the importance of cis ‐acting lncRNAs in TLR signaling, innate immunity, and pathophysiological inflammation. Synopsis: Activation of Toll‐like receptors (TLRs) induced expression changes in lncRNAs that regulate their neighboring genes involved in inflammation. A lncRNA named ROCKI forms a ribonucleoprotein complex and controls inflammatory responses via chromatin modification. More than 200 cis ‐acting lncRNAs and protein‐coding gene pairs were identified in TLR‐stimulated macrophages. Lnc‐MARCKS, also designated ROCKI, is a master regulator of inflammatory responses to TLR ligands. ROCKI interacts with APEX1 and HDAC1 enzymes at the MARCKS promoter. ROCKI expression is significantly associated with inflammation‐ and infection‐related disease phenotypes in humans. Abstract : Genome‐wide identification of cis ‐acting lncRNAs that regulate gene expression in response to infection identify a Toll‐like receptor‐induced upstream regulator of calcium signalling and inflammation processes, associated with inflammatory or infectious disease pathologies in humans.